The origin of biological information and programmed protein synthesis - Liu, Dan (Scientific Research Publishing, 2013)
Biological information is one of the most important characteristics of life, and it enables life to evolve to higher complexity and adapt to the environment by mutation and natural selection. However, the origin of this information recording and retrieval system remains a mystery. To understand the origin of biological information will lead us to one step closer to understand the origin of life on earth. Biological information is encoded in DNA and translated into protein by the ribosome in all free living organisms. The information has to be translated into proteins to carry out its biological functions, so the evolution of the ribosome must be integrated with the development of biological information. In this article, I propose that the small ribosomal subunit evolved from a ribozyme that acted as an RNA helicase in the ancient RNA world, and the involvement of tRNAs and the large ribosomal subunit evolved to enhance the helicase activity and to overcome the higher energy require-ment for high GC content RNA helices. This process could have developed as a primitive recording mechanism: since Watson-Crick base paring is a natural property of RNA, each time the proto-small ribosomal subunit came to a particular GC-rich helix, tRNA-like molecules and the proto-large ribosomal subunit would have to be engaged to generate the helicase activity, and consequently the same polypeptide would be synthesized as a by-product. Simple recorded messages then evolved into useful biological information through continuous mutation and natu-ral selection. This hypothesis provides logical and incremental steps for the development of programmed protein synthesis. I also argue that the helicase activity is preserved in the modern ribosome and that from our knowledge of the ribosome, and we can deduce the possible mechanisms of the helicase activity.
Keywords: Ribosome; tRNA; Translation; Translocation; mRNA Helicase; Evolution; Origin of Biological Information